2019
DOI: 10.1002/pat.4788
|View full text |Cite
|
Sign up to set email alerts
|

Great improvement of low‐temperature impact resistance of isotactic polypropylene/ethylene propylene diene monomer rubber blends by traces of carbon nanotubes and β‐nucleating agents

Abstract: In this work, a considerable low-temperature toughness enhancement of isotactic polypropylene (iPP) was achieved by adding 30 wt% ethylene propylene diene monomer rubber (EPDM) as well as traces of β-nucleating agent (β-NAs) and carbon nanotubes (CNTs). The impact strength of the iPP/30 wt% EPDM blend with 0.1 wt% β-NAs reached 6.57 kJ/m 2 at −20°C, over 2.5 times of pure iPP. A slightly improved impact strength was further found in the β-nucleated iPP/30 wt% EPDM at the presence of 0.05 wt% CNTs. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…They stated that POE rubber is an effective toughening agent that makes the brittle PP polymer more ductile and tough (Lim et al, 2006;Lendvai, 2021). The rubber particles, in addition to promoting crazing (Farhang and Bagheri, 2014) and shear yielding, can also improve the fracture resistance of PP by varying its crystalline structure (Jang et al, 1985;Fan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They stated that POE rubber is an effective toughening agent that makes the brittle PP polymer more ductile and tough (Lim et al, 2006;Lendvai, 2021). The rubber particles, in addition to promoting crazing (Farhang and Bagheri, 2014) and shear yielding, can also improve the fracture resistance of PP by varying its crystalline structure (Jang et al, 1985;Fan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of the mechanical properties obtained from room temperature (RT) cannot be simply transferred to the cryogenic case. Thus, for cryogenic engineering applications, it is important and necessary to study the relative properties of PP composites at cryogenic temperature (CT) 5,6 . For PP‐based composites, polymer chains are easily frozen at CT, making them unable to have the same chain flexibility as in RT environment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that basalt fiber can prevent PP from plastically deforming, and nano‐clay can resist microcrack propagation in the matrix, and the impact strength of PP composites can be increased by 62.5%. Fan et al 6 introduced carbon nanotubes, β‐nucleating agent, and ethylene propylene diene monomer rubber into the PP composites, which ultimately increased the impact strength of the PP composites by more than 2.5 times at − 20°C.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, V fc is corresponding to the lowest modulus loss for the toughened polymers. In addition, the impact modifier can affect the V fc value, which has been extensively studied in terms of modifier materials, 28–33 shape, 34 sizes, 35–40 and modulus 41–43 …”
Section: Introductionmentioning
confidence: 99%